2017
DOI: 10.1021/acs.cgd.6b01534
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphs and Hydrates of Sequifenadine Hydrochloride: Crystallographic Explanation of Observed Phase Transitions and Thermodynamic Stability

Abstract: In this study, detailed analysis of crystal structures was used to rationalize the observed stability and phase transformations of sequifenadine hydrochloride polymorphs and hydrates, as well as to understand the observed structural diversity. The performed polymorph and hydrate screening revealed the existence of six polymorphs and four hydrates. Crystal structures of these phases were determined either from single crystal or from powder diffraction data. The different possibilities for packing of sequifenadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…On the one hand, a high tendency to form solvates will limit the possibilities to prepare the unsolvated phase(s) of a compound. On the other hand, desolvation of solvates often produces new polymorphs which cannot be obtained using conventional crystallization techniques. Despite the fact that new polymorphs obtained using desolvation are reported rather often, it is common that their crystal structures remain undetermined, as usually the polymorphs are obtained in the form of a powder. Nevertheless, the advancement of crystal structure determination from powder diffraction by using direct-space methods complemented by DFT-D calculations ,, or from electron diffraction measurements , is being successfully used more and more often for crystal structure determination.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, a high tendency to form solvates will limit the possibilities to prepare the unsolvated phase(s) of a compound. On the other hand, desolvation of solvates often produces new polymorphs which cannot be obtained using conventional crystallization techniques. Despite the fact that new polymorphs obtained using desolvation are reported rather often, it is common that their crystal structures remain undetermined, as usually the polymorphs are obtained in the form of a powder. Nevertheless, the advancement of crystal structure determination from powder diffraction by using direct-space methods complemented by DFT-D calculations ,, or from electron diffraction measurements , is being successfully used more and more often for crystal structure determination.…”
Section: Introductionmentioning
confidence: 99%
“…Hydration or dehydration processes may occur unexpectedly during drug development, manufacturing, storage, and pharmaceutical preparation and could affect the qualities of the final products. , Hence, it is of great significance to investigate the relative stabilities of the hydrates and figure out the phase transformation processes between hydrates and corresponding neat forms. Previous studies have indicated that the stability of hydrates is closely related to the humidity, water activity in the solvent, and temperature. , Liu et al investigated the transformation water activity and concluded that the transformation water activity ratio of different crystal forms of theophylline was inversely proportional to the solubility ratio at a certain temperature. Ito et al found that the anhydrate of antibiotic clarithromycin reversibly transformed to dihydrate when relative humidity (RH) increased to 60% and then transformed to trihydrate at 95% RH.…”
Section: Introductionmentioning
confidence: 99%
“…1 Finally, the formation of hydrates tends to decrease the void space in a crystal structure and leads to more efficient packing. 9,15 Figure 1. The molecular structure of quercetin In this work, quercetin, 2-(3,4-Dihydroxyphenyl)-3,5,7-trihydroxy-4H-chromen-4-one, is chosen as the model compound.…”
Section: Introductionmentioning
confidence: 99%